Development of a defined synthetic medium to mimic sugarcane molasses for ethanol fermentation. - Cunha, Gabriel Caetano de Gois e (2022)
Ethanol production in Brazil occurs through the fermentation of sugarcane juice or molasses by yeasts of the species Saccharomyces cerevisiae. The use of molasses has logistical and economic advantages compared to sugar cane juice, due to its reduced moisture content and high concentration of sugars. However, the quality of the molasses varies even in the same mill, depending on factors such as the quality of the cane, fertilization and the number of recycling to which the molasses was submitted for sugar removal. For this reason, the use of molasses for academic research becomes problematic because it is not possible to guarantee that a given lot of molasses is representative and thus, the reproducibility of experiments is impaired, making its use difficult by research centers. Thus, the objective of this work is to develop a defined medium that is able to reproduce physiological and technological parameters from real molasses. As the first iteration of this medium to be proposed, a published semi-synthetic medium intended to simulate sugar cane molasses must was tested in two industrial lines and two laboratory strains of S. cerevisiae and not able to adequately reproduce the batch growths for the four distinct strains compared to real molasses from sugarcane mills. Thus, the medium was adapted, generating the 1SMol synthetic medium, which had its composition divided into seven nutritional groups that had their effects on the growth of an industrial yeast strain (PE-2) and a laboratory strain (CEN.PK113-7D) in microplate batch growth experiments. The nutritional groups that most impacted the specific growth rate and maximum absorbance were vitamins and the nitrogen source. However, when compared to real molasses, 1SMol presents high specific growth velocity values lower than real molasses. The medium was then adapted, generating 2SMol, a defined medium, with results in simple batches similar to industrial molasses. For this medium, it was observed that the options of vitamins, ammonium and amino acids have had a greater impact on growth parameters in batches. The 2SMol medium was then used in a batch-fed experiment with cell recycling, simulating the Brazilian industrial process of ethanol production, obtaining results similar to the three industrial molasses regarding viability parameters, wine pH, ethanol yield, profile of CO2 and biomass production over five cycles. Thus, the 2SMol medium is presented as a good alternative as a standard medium for carrying out studies involving the fermentation of sugarcane molasses by yeast.